Hole transport layer-free perovskite solar cells based on halogenated copper chelate additives and methods of making

CN119836100BActive Publication Date: 2026-10-27东方电气长三角(杭州)创新研究院有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411828141.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2026-10-27
Estimated Expiration
2044-12-12

Smart Images

  • Figure CN119836100B_ABST
    Figure CN119836100B_ABST
Patent Text Reader

Abstract

The application relates to a halogenated copper chelate additive-based perovskite solar cell without a hole transport layer and a preparation method, the perovskite solar cell is from bottom to top a transparent conductive substrate layer, a perovskite light-absorbing layer, an electron transport layer, an interface buffer layer and an electrode layer, wherein the perovskite light-absorbing layer contains a halogenated copper chelate additive. The structural general formula of the halogenated copper chelate is M.N, wherein M is halogenated copper, and N is a thioamide compound. The halogenated copper chelate additive is used to precisely control the perovskite film growth process, a gradient energy band structure beneficial to interface charge transport is constructed, the hole migration at the perovskite and the transparent conductive substrate is enhanced, the hole transport from the perovskite layer to the transparent electrode is accelerated, the carrier recombination is effectively inhibited, and finally a perovskite solar cell with a simple structure and excellent performance is prepared, thereby providing a new solution for the development of the perovskite solar cell without a hole transport layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell technology, and in particular to a hole-transport layer-free perovskite solar cell based on copper halide chelate additives and its preparation method. Background Technology

[0002] Organometal halide perovskites, as promising photovoltaic materials, have attracted global research attention in recent years due to their significant advantages such as low exciton binding energy, long carrier lifetime, high light absorption capacity, and tunable bandgap. Significant progress has been made in the research of inverted perovskite solar cells in recent years, with efficiencies reaching 26.7%. However, hole transport efficiency has a significant impact on the performance of inverted perovskite solar cell devices, and currently, the stability and scale-up fabrication process of inverted perovskite devices are limited by the hole transport layer. Commonly used hole transport layer materials can be divided into organic and inorganic materials. Organic hole transport materials, such as [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphoric acid (Me-4PACz), have high cost, poor conductivity, and hydrophobic properties that make it difficult to uniformly coat perovskite solutions on their surface. They may also degrade under light and high temperature conditions. Inorganic hole transport materials, such as nickel oxide, often require relatively high annealing temperatures to achieve high-quality crystallization and high hole transport efficiency. Furthermore, nickel oxide exhibits interfacial degradation reactions with perovskite, which is detrimental to the long-term stable operation of devices.

[0003] To address the shortcomings of hole transport layer materials, existing technologies have proposed hole transport layer-free solutions. The main method involves removing the hole transport layer between the transparent conductive oxide and the perovskite, leading to direct contact between the transparent conductive oxide and the perovskite, forming a Schottky contact barrier. Defects at the contact interface generate a Fermi pinning effect, causing the loss region and bandgap to bend downwards, hindering effective hole transport. At the same time, the removal of the hole transport layer causes the interface contact to lose selectivity, exacerbating the voltage reduction of the non-radiative recombination perovskite solar cell between electrons and holes.

[0004] Selecting a suitable p-type hole transport layer material to add to the perovskite precursor solution to prepare a composite perovskite solution, and developing a rapid fabrication method for perovskite solar cell devices without a hole transport layer, are crucial for achieving high-efficiency, stable, and low-cost perovskite solar cells. Although attempts have been made to prepare perovskite solar cells without a hole transport layer by doping perovskite precursor solutions with p-type semiconductor molecules such as CuSCN, CuCl, and Cu(Tu)I, their photoelectric conversion efficiency is still lower than that of perovskite solar cells with a complete structure. This is mainly because the work function mismatch at the interface between perovskite and transparent conductive oxide electrodes makes it difficult to effectively extract holes, resulting in severe charge recombination problems. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives and its preparation method. Copper halide chelate molecules are squeezed from the precursor solution to the perovskite grain boundaries and the bottom of the thin film, achieving P-type doping of the buried interface perovskite thin film, improving the interface hole extraction and transport capabilities, and improving the film quality of the perovskite light-absorbing layer. This significantly improves the efficiency, stability, and process reproducibility of hole-transport layer-free perovskite solar cells.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: As a first aspect, a hole-transport layer-free perovskite solar cell based on copper halide chelate additive is provided, wherein the perovskite solar cell comprises, from bottom to top, a transparent conductive substrate layer, a perovskite light-absorbing layer, an electron transport layer, an interface buffer layer, and an electrode layer, wherein the perovskite light-absorbing layer contains copper halide chelate additive.

[0007] As a second aspect, a method for preparing the hole-transport layer-free perovskite solar cell based on copper halide chelate additives is provided, comprising the following steps:

[0008] (1) Synthesis of copper halide chelates;

[0009] (2) Dissolve perovskite powder in an organic solvent, stir and clarify to form a perovskite precursor solution, such that the concentration of perovskite in the perovskite precursor solution is 0.1-3 mol / L; add copper halide chelate, and after complete dissolution, obtain a perovskite precursor solution containing copper halide chelate additive, such that the concentration of copper halide chelate additive in the perovskite precursor solution containing copper halide chelate additive is 0.001-50 mg / mL; coat or print the perovskite precursor solution containing copper halide chelate additive on a clean transparent conductive substrate, and obtain a perovskite light-absorbing layer after heat treatment.

[0010] (3) An electron transport layer, an interface buffer layer and an electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell based on copper halide chelate additives.

[0011] Furthermore, the heat treatment temperature of the perovskite light-absorbing layer is 30–300°C, and the time is 3–120 min, preferably 100°C for 16 min.

[0012] Further, the transparent conductive substrate layer is selected from: FTO (fluorine-doped tin oxide) glass, ITO (tin-doped indium oxide) glass, ITO (tin-doped indium oxide) / PET (ethylene terephthalate), ITO (tin-doped indium oxide) / PEN (polyethylene phthalate), and ITO (tin-doped indium oxide) / PI (polyimide); the electron transport layer is fullerene and its derivatives, selected from: C60, C70, and PC60M; the interface buffer layer is selected from: copper bath, tin oxide, zinc oxide, yttrium oxide, cerium oxide, titanium oxide, and niobium oxide; the electrode layer is selected from: Cu, Ag, Au, Mo, ITO (tin-doped indium oxide), IZO (zinc-doped indium oxide), and AZO (aluminum-doped zinc oxide).

[0013] Furthermore, the perovskite has the general structural formula ABX3, where A is selected from Cs. + MA + (CH3NH3 + ), FA + [HC(NH2)NH2 + B is selected from Pb 2+ Sn 2+ 、Ge 2+ X is selected from I - ,Br - Cl - The general structural formula of the copper halide chelate is M·N, where M is copper halide selected from: CuF, CuCl, CuBr, CuI, CuBF4, CuPF6, and N is a thioamide compound selected from: thioaminourea, 3,4,5,6-tetrahydro-2-pyrimidinethiol, amidothiourea, thioformyldihydrazide, thiocaprolactam, thioisonicotinamide, triethylenethiophosphoramide, dithiobiurea, 1,1-thiocarbonyldiimidazole, 1H-indole-4-thioformamide, pyrazine-2-thioamide, pyrimidine-2-carbonthioamide, ethylenethiourea, and tetrahydropyrrole-2-thione.

[0014] Preferably, the copper halide chelate is CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol.

[0015] Furthermore, the thickness of the perovskite light-absorbing layer containing copper halide chelate additives is 100–2000 nm; the thickness of the electron transport layer is 1–100 nm; the thickness of the interface buffer layer is 1–100 nm; and the thickness of the electrode layer is 10–10000 nm.

[0016] Furthermore, the electron transport layer is deposited by vapor deposition; the interface buffer layer is deposited by vapor deposition, sputtering, reactive plasma deposition, chemical vapor deposition, coating, or printing; the electrode layer is deposited by vapor deposition, sputtering, chemical vapor deposition, coating, or printing.

[0017] Preferably, the transparent conductive substrate layer is FTO glass; the electron transport layer is C60; the interface buffer layer is tin oxide; and the electrode layer is IZO.

[0018] Preferably, the thickness of the perovskite light-absorbing layer containing copper halide chelate additive is 530 nm; the thickness of the electron transport layer is 15 nm; the thickness of the interface buffer layer is 10 nm; the thickness of the electrode layer is 400 nm; the electron transport layer is deposited by vapor deposition; the interface buffer layer is deposited by reactive plasma deposition; and the electrode layer is deposited by sputtering deposition.

[0019] Furthermore, the organic solvent used to prepare the perovskite precursor solution is one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol, acetonitrile, and tetrahydrofuran mixed in any proportion.

[0020] Preferably, the concentration of perovskite in the perovskite precursor solution is 1.45 mol / L; the concentration of copper halide chelate additive in the perovskite precursor solution containing copper halide chelate additive is 3.3 mg / mL; and the organic solvent used to prepare the perovskite precursor solution is a mixture of acetonitrile, tetrahydrofuran, and dimethyl sulfoxide in a volume ratio of 6:1:3.

[0021] The beneficial effects of this invention are:

[0022] 1. The copper halide chelate material additive selected in this invention participates in the crystal lattice formation of perovskite. It can act as a seed crystal in the perovskite precursor solution, forming heterogeneous nucleation sites with large crystal nuclei. These sites can reduce the nucleation free energy of PbI2, ultimately promoting the growth of perovskite crystals, increasing the grain size of the perovskite film, making the perovskite film more uniform and dense, improving the quality of the film and reducing grain boundary defects.

[0023] 2. Copper halide chelates interact strongly with uncoordinated lead ions in perovskites. The S and N atoms with lone pairs of electrons in the molecule can move towards the net positively charged, incompletely coordinated Pb atoms. 2+ This provides electron density, accelerating efficient charge transfer between the copper halide chelate and the perovskite. Furthermore, the -Cl, C=S, and amine groups in the copper halide chelate molecule can also interact with the perovskite, which is beneficial for filling shallow-level iodine vacancy defects generated during perovskite film formation.

[0024] 3. This invention utilizes the self-adsorption properties of copper halide chelate materials to promote hole transport at the interface between perovskite and transparent conductive substrate and reduce non-radiative recombination. It also adjusts the work function at the interface between perovskite and transparent conductive substrate to make the energy levels more matched, reduce the hole transport energy barrier, and realize the preparation of a highly efficient and stable perovskite solar cell without a hole transport layer.

[0025] 4. This invention uses copper halide chelates to prepare hole-transport-free perovskite solar cells. The process is simple, low-cost, and can be scaled up for mass production, which is conducive to industrialization. Attached Figure Description

[0026] The present invention will be further described below with reference to the accompanying drawings and embodiments;

[0027] Figure 1 This is a schematic diagram of the perovskite solar cell structure based on copper halide chelate additives according to the present invention.

[0028] Figure 2 SEM image of the perovskite light-absorbing layer with CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol additive of the present invention.

[0029] Figure 3 This is the steady-state fluorescence spectrum of the perovskite absorber layer with and without copper halide chelate additives according to the present invention.

[0030] In the figure, 1 is a transparent conductive substrate, 2 is a perovskite light-absorbing layer, 3 is an electron transport layer, 4 is an interface buffer layer, 5 is an electrode layer, and 6 is a copper halide chelate additive. Detailed Implementation

[0031] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention.

[0032] The idea behind this invention is to precisely control the growth process of perovskite thin films using copper halide chelate additives, construct a gradient band structure that is conducive to interfacial charge transport, enhance hole migration at the perovskite and transparent conductive substrate, accelerate hole transport from the perovskite layer to the transparent electrode, effectively suppress carrier recombination, and ultimately fabricate a perovskite solar cell with a simple structure and excellent performance, providing a new solution for the development of hole-free pure transport layer perovskite solar cells.

[0033] Example 1:

[0034] like Figure 1 As shown, a hole-transport-layer-free perovskite solar cell based on copper halide chelate additives and its preparation method include the following steps:

[0035] Step 1: The steps for synthesizing CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol:

[0036] Under a nitrogen atmosphere, a solution of 3,4,5,6-tetrahydro-2-pyrimidinethiol (containing 697.08 mg of 3,4,5,6-tetrahydro-2-pyrimidinethiol dissolved in 30 mL of acetonitrile) and a cuprous chloride (CuCl) solution (containing 594 mg of cuprous chloride dissolved in 10 mL of acetonitrile) were mixed and stirred continuously for 1 hour. After the resulting suspension was allowed to stand for 3 days, CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol solid precipitated out. The CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol solid was filtered and washed three times with acetonitrile and diethyl ether, respectively. Finally, it was dried under vacuum at 70 °C for 12 hours to obtain white CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol powder (697 mg, yield 54%).

[0037] Step 2: Preparation of a hole-transport layer-free perovskite solar cell containing CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol additive:

[0038] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0039] (2) First, weigh CsI, MAI, FAI, and PbI2 (molar ratio of 0.1:0.1:0.8:1.05) powder and dissolve them in a mixed solvent of acetonitrile, tetrahydrofuran, and dimethyl sulfoxide in a volume ratio of 6:1:3. After stirring and clarifying, a 1.45 mol / L perovskite precursor solution is obtained. Then, weigh 3.3 mg of CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol and add it to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol additive is obtained.

[0040] (3) A perovskite precursor solution containing CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol additive was slit-coated on a clean FTO glass substrate. The coated perovskite wet film was heat-treated at 100°C for 16 min to obtain a perovskite light-absorbing layer with a thickness of 530 nm.

[0041] (4) A 15 nm thick C60 electron transport layer, a 10 nm thick tin oxide interface buffer layer, and a 400 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a hole-transport layer-free perovskite solar cell based on CuCl·3,4,5,6-tetrahydro-2-pyrimidine thiol additive.

[0042] Comparative Example 1:

[0043] A perovskite solar cell without a hole transport layer and a method thereof for preparation thereof, comprising the following steps:

[0044] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0045] (2) First, weigh CsI, MAI, FAI, and PbI2 (molar ratio of 0.1:0.1:0.8:1.05) powder and dissolve them in a mixed solvent of acetonitrile, tetrahydrofuran, and dimethyl sulfoxide in a volume ratio of 6:1:3. After stirring and clarifying, a 1.45 mol / L perovskite precursor solution is obtained. After stirring and dissolving completely, a perovskite precursor solution without copper halide chelate additives is obtained.

[0046] (3) A perovskite precursor solution was slit-coated on a clean FTO glass substrate, and the coated perovskite wet film was heat-treated at 100°C for 16 min to obtain a perovskite light-absorbing layer with a thickness of 530 nm.

[0047] (4) A 15 nm thick C60 electron transport layer, a 10 nm thick tin oxide interface buffer layer, and a 400 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a hole-transport layer-free perovskite solar cell based on copper halide chelate additive.

[0048] Comparative Example 2:

[0049] Step 1: The steps for synthesizing CuCl·1,1-thiocarbonyldiimidazole:

[0050] Under a nitrogen atmosphere, a 1,1-thiocarbonyldiimidazole solution (containing 1069.26 mg of 1,1-thiocarbonyldiimidazole dissolved in 30 mL of acetonitrile) and a cuprous chloride (CuCl) solution (containing 594 mg of cuprous chloride dissolved in 10 mL of acetonitrile) were mixed and stirred continuously for 1 hour. After the resulting suspension was allowed to stand for 3 days, CuCl·1,1-thiocarbonyldiimidazole solid precipitated out. The CuCl·1,1-thiocarbonyldiimidazole solid was filtered and washed three times with acetonitrile and diethyl ether in sequence. Finally, it was dried under vacuum at 70 °C for 12 hours to obtain white CuCl·1,1-thiocarbonyldiimidazole powder (1031 mg, yield 62%).

[0051] Step 2: Preparation of a hole-transport layer-free perovskite solar cell containing CuCl·1,1-thiocarbonyldiimidazole additive:

[0052] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0053] (2) First, weigh CsI, MAI, FAI, and PbI2 (molar ratio of 0.1:0.1:0.8:1.05) powder and dissolve them in a mixed solvent of acetonitrile, tetrahydrofuran, and dimethyl sulfoxide in a volume ratio of 6:1:3. After stirring and clarifying, a 1.45 mol / L perovskite precursor solution is obtained. Then, weigh 3.3 mg of CuCl·1,1-thiocarbonyldiimidazole and add it to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing CuCl·1,1-thiocarbonyldiimidazole additive is obtained.

[0054] (3) A perovskite precursor solution containing CuCl·1,1-thiocarbonyldiimidazole additive was slit-coated on a clean FTO glass substrate. The coated perovskite wet film was heat-treated at 100°C for 16 min to obtain a perovskite light-absorbing layer with a thickness of 530 nm.

[0055] (4) A 15 nm thick C60 electron transport layer, a 10 nm thick tin oxide interface buffer layer, and a 400 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a hole-transport layer-free perovskite solar cell based on CuCl·1,1-thiocarbonyldiimidazole additive.

[0056] Comparative Example 3:

[0057] Step 1: The steps for synthesizing CuCl·triethylenethiophosphoramide:

[0058] Under a nitrogen protective atmosphere, a triethylenethiophosphoramide solution (containing 1135.32 mg of triethylenethiophosphoramide dissolved in 30 mL of acetonitrile) and a cuprous chloride (CuCl) solution (containing 594 mg of cuprous chloride dissolved in 10 mL of acetonitrile) were mixed and stirred continuously for 1 hour. After the resulting suspension was allowed to stand for 3 days, CuCl·triethylenethiophosphoramide solid precipitated out. The CuCl·triethylenethiophosphoramide solid was filtered and washed three times with acetonitrile and diethyl ether in sequence. Finally, it was vacuum dried at 70 °C for 12 hours to obtain white CuCl·triethylenethiophosphoramide powder (830 mg, yield 48%).

[0059] Step 2: Preparation of a hole-transport layer-free perovskite solar cell containing CuCl·triethylenethiophosphoramide additive:

[0060] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0061] (2) First, weigh CsI, MAI, FAI, and PbI2 (molar ratio of 0.1:0.1:0.8:1.05) powder and dissolve them in a mixed solvent of acetonitrile, tetrahydrofuran, and dimethyl sulfoxide in a volume ratio of 6:1:3. After stirring and clarifying, a 1.45 mol / L perovskite precursor solution is obtained. Then, weigh 3.3 mg of triethylenethiophosphoramide and add it to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing CuCl·triethylenethiophosphoramide additive is obtained.

[0062] (3) A perovskite precursor solution containing CuCl·triethylenethiophosphoramide additive was slit-coated on a clean FTO glass substrate. The coated perovskite wet film was heat-treated at 100°C for 16 min to obtain a perovskite light-absorbing layer with a thickness of 530 nm.

[0063] (4) A 15 nm thick C60 electron transport layer, a 10 nm thick tin oxide interface buffer layer, and a 400 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a hole-transport layer-free perovskite solar cell based on CuCl·triethylenethiophosphoramide additive.

[0064] Comparative Example 4:

[0065] Step 1: The steps for synthesizing CuCl·thioformyl dihydrazide:

[0066] Under a nitrogen atmosphere, a solution of thiocarbamate dihydrazide (containing 636.9 mg of thiocarbamate dihydrazide dissolved in 30 mL of acetonitrile) and a cuprous chloride (CuCl) solution (containing 594 mg of cuprous chloride dissolved in 10 mL of acetonitrile) were mixed and stirred continuously for 1 hour. After the resulting suspension was allowed to stand for 3 days, CuCl·thiocarbamate dihydrazide solid precipitated out. The CuCl·thiocarbamate dihydrazide solid was filtered and washed three times with acetonitrile and diethyl ether in sequence. Finally, it was vacuum dried at 70 °C for 12 hours to obtain white CuCl·thiocarbamate dihydrazide powder (837 mg, yield 68%).

[0067] Step 2: The steps for preparing a hole-transport layer-free perovskite solar cell containing CuCl·thiocarbamoyl dihydrazine additive:

[0068] (1) The FTO glass was ultrasonically cleaned sequentially with glass cleaning agent, ultrapure water and alcohol, and dried after cleaning to obtain a clean FTO glass substrate.

[0069] (2) First, weigh CsI, MAI, FAI, and PbI2 (molar ratio of 0.1:0.1:0.8:1.05) powder and dissolve them in a mixed solvent of acetonitrile, tetrahydrofuran, and dimethyl sulfoxide in a volume ratio of 6:1:3. After stirring and clarifying, a 1.45 mol / L perovskite precursor solution is obtained. Then, weigh 3.3 mg of CuCl·thiocarbamate dihydrazide and add it to 1 mL of the perovskite precursor solution. After stirring and dissolving completely, a perovskite precursor solution containing CuCl·thiocarbamate dihydrazide additive is obtained.

[0070] (3) A perovskite precursor solution containing CuCl·thiocarbamate dihydrazide additive was slit-coated on a clean FTO glass substrate. The coated perovskite wet film was heat-treated at 100°C for 16 min to obtain a perovskite light-absorbing layer with a thickness of 530 nm.

[0071] (4) A 15 nm thick C60 electron transport layer, a 10 nm thick tin oxide interface buffer layer, and a 400 nm thick IZO electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a hole-transport layer-free perovskite solar cell based on CuCl·thiocarbazide additive.

[0072] As shown in Table 1, the perovskite solar cell without a hole transport layer prepared with CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol additive has a photoelectric conversion efficiency of up to 25.14%, and the efficiency of the cell only decreases by 1.4% after 1000 hours of maximum power point tracking. The device efficiency and stability are far superior to other comparative devices, indicating that CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol additive can significantly improve the efficiency and stability of perovskite solar cells without a hole transport layer.

[0073] Figure 2 The perovskite films with added CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol exhibit large grain sizes, high phase purity, and crystallinity, retaining a well-preserved crystal structure, thus significantly improving the quality of the perovskite films. Because the doping amount of the copper halide chelate is relatively small, it does not damage the original perovskite structure; instead, the perovskite structure becomes more stable.

[0074] like Figure 3 As shown, steady-state fluorescence testing further evaluated that the band gap of the perovskite after adding CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol did not change, and the fluorescence intensity was relatively high, indicating that CuCl·3,4,5,6-tetrahydro-2-pyrimidinethiol has excellent defect passivation effect, which can effectively increase charge carrier lifetime and reduce charge carrier recombination.

[0075] Table 1. Performance parameters of devices in the examples and comparative examples

[0076]

[0077]

[0078] The above description is merely a preferred experimental example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A perovskite solar cell without a hole transport layer based on copper halide chelate additives, characterized in that, The perovskite solar cell consists of, from bottom to top, a transparent conductive substrate layer, a perovskite light-absorbing layer, an electron transport layer, an interface buffer layer, and an electrode layer, wherein the perovskite light-absorbing layer contains a copper halide chelate additive. The copper halide chelate is formed by chelating copper halide M and a thioamide compound N. M is selected from CuF, CuCl, CuBr, CuI, CuBF4 or CuPF6, and N is a thioamide compound selected from: thioaminourea, 3,4,5,6-tetrahydro-2-pyrimidinethiol, amidothiourea, thioformyldihydrazide, thiocaprolactam, thioisonicotinamide, triethylenethiophosphoramide, dithiobiurea, 1,1-thiocarbonyldiimidazole, 1H-indole-4-thioformamide, pyrazine-2-thioamide, pyrimidine-2-carbonthioamide, ethylenethiourea, and tetrahydropyrrole-2-thione.

2. A method for preparing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives as described in claim 1, characterized in that, Includes the following steps: (1) Synthesis of copper halide chelates; (2) Dissolve the perovskite powder in an organic solvent, stir and clarify to form a perovskite precursor solution, so that the concentration of perovskite in the perovskite precursor solution is 0.1-3 mol / L; add copper halide chelate, and after complete dissolution, obtain a perovskite precursor solution containing copper halide chelate additive, so that the concentration of copper halide chelate additive in the perovskite precursor solution containing copper halide chelate additive is 0.001-50 mg / mL; coat or print the perovskite precursor solution containing copper halide chelate additive on a clean transparent conductive substrate, and obtain a perovskite light-absorbing layer after heat treatment. (3) An electron transport layer, an interface buffer layer and an electrode layer are sequentially deposited on the perovskite light-absorbing layer to obtain a perovskite solar cell based on copper halide chelate additives.

3. The method for preparing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives as described in claim 2, characterized in that, The heat treatment temperature of the perovskite light-absorbing layer is 30–300 °C, and the time is 3–120 min.

4. The method for preparing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives as described in claim 2, characterized in that, The transparent conductive substrate layer is selected from: FTO glass, ITO glass, ITO / PET, ITO / PEN, ITO / PI; the electron transport layer is fullerene and its derivatives, selected from: C60, C70, PC60M; the interface buffer layer is selected from: copper bath, tin oxide, zinc oxide, yttrium oxide, cerium oxide, titanium oxide, niobium oxide; the electrode layer is selected from: Cu, Ag, Au, Mo, ITO, IZO, AZO.

5. The method for preparing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives as described in claim 2, characterized in that, The perovskite has the general structural formula ABX3, where A is selected from Cs. + MA + FA + B is selected from Pb 2+ Sn 2+ 、Ge 2+ X is selected from I - ,Br - Cl - The general structural formula of the copper halide chelate is M•N, where M is copper halide selected from: CuF, CuCl, CuBr, CuI, CuBF4, CuPF6, and N is a thioamide compound selected from: thioaminourea, 3,4,5,6-tetrahydro-2-pyrimidinethiol, amidothiourea, thioformyldihydrazide, thiocaprolactam, thioisonicotinamide, triethylenethiophosphoramide, dithiobiurea, 1,1-thiocarbonyldiimidazole, 1H-indole-4-thioformamide, pyrazine-2-thioamide, pyrimidine-2-carbonthioamide, ethylenethiourea, and tetrahydropyrrole-2-thione.

6. The method for preparing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives as described in claim 2, characterized in that, The thickness of the perovskite light-absorbing layer containing copper halide chelate additives is 100–2000 nm; the thickness of the electron transport layer is 1–100 nm; the thickness of the interface buffer layer is 1–100 nm; and the thickness of the electrode layer is 10–10000 nm.

7. The method for preparing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives as described in claim 2, characterized in that, The electron transport layer is deposited by vapor deposition. The deposition methods for the interface buffer layer include: evaporation, sputtering, reactive plasma deposition, chemical vapor deposition, coating, and printing; the deposition methods for the electrode layer include: evaporation, sputtering, chemical vapor deposition, coating, and printing.

8. The method for preparing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives as described in any one of claims 4-7, characterized in that, The transparent conductive substrate is FTO glass; the electron transport layer is C60; the interface buffer layer is tin oxide; the electrode layer is IZO; the thickness of the perovskite light-absorbing layer containing copper halide chelate additive is 530 nm; the thickness of the electron transport layer is 15 nm; the thickness of the interface buffer layer is 10 nm; the thickness of the electrode layer is 400 nm; the electron transport layer is deposited by vapor deposition; the interface buffer layer is deposited by reactive plasma deposition; the electrode layer is deposited by sputtering deposition; the copper halide chelate is CuCl•3,4,5,6-tetrahydro-2-pyrimidinethiol.

9. The method for preparing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives as described in claim 2, characterized in that, The organic solvent used to prepare the perovskite precursor solution is one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, 2-methoxyethanol, acetonitrile, and tetrahydrofuran mixed in any proportion.

10. The method for preparing a hole-transport layer-free perovskite solar cell based on copper halide chelate additives as described in claim 2 or 9, characterized in that, The concentration of perovskite in the perovskite precursor solution is 1.45 mol / L; the concentration of copper halide chelate additive in the perovskite precursor solution containing copper halide chelate additive is 3.3 mg / mL; the organic solvent used to prepare the perovskite precursor solution is a mixture of acetonitrile, tetrahydrofuran, and dimethyl sulfoxide in a volume ratio of 6:1:3.

Citation Information

Patent Citations

  • Preparation method of perovskite solar cell carbon back electrode

    CN109742244A

  • Cuprous iodide, preparation method thereof and trans-perovskite solar cell

    CN118419963A